DESIGNING A PERFORMANCE APPRAISAL SYSTEM FOR MANAGEMENT CONSULTANT OFFICE “D” - Susanto, Susanto; Darmasetiawan, Noviaty Kresna (Dinasti International Journal of Digital Business Management, 2020)
This design aims to conduct a job analysis and designing a performance appraisal system for Management Consultant Office "D". The constructionism approach used in this design that presents a structured and systematic analysis by describing the steps of designing a performance appraisal system through data collection methods: interviews, direct observation and document analysis. A summary of the findings shows that the Management Consultant Office "D" has never done a job analysis for each level of position in the organization and don’t have a performance appraisal system. Therefore, a job analysis is performed for each level of position and neatly formatted in the job analysis table. The results of this design are in the form of job analysis, determination of the performance appraisal dimensions and their weighting which are made into the format of the performance appraisal form along with the procedures and the procedures for carrying out the performance appraisal.